2007
DOI: 10.1029/2006ja012191
|View full text |Cite
|
Sign up to set email alerts
|

Jovian S burst generation by Alfvén waves

Abstract: [1] Jupiter's radio emissions are dominated in intensity by decametric radio emissions due to the Io-Jupiter interaction. Previous analyses suggest that these emissions are cyclotron-maser emissions in the flux tubes connecting Io or Io's wake to Jupiter. Electrons responsible for the emission are thought to be accelerated from Io to Jupiter. We present simulations of this hot electron population under the assumption of acceleration by Alfvén waves in the Io flux tube. Outside of limited acceleration regions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 30 publications
(51 reference statements)
10
93
0
Order By: Relevance
“…Recent works have been specifically devoted to non-MHD effects [Tsiklauri et al, 2005;McClements and Fletcher, 2009;Bian and Kontar, 2011]. There are also observational evidences that Alfvén waves can accelerate electrons in the vicinity of Io and Jupiter [Hess et al, 2007] sometimes combined with other acceleration structures [Hess et al, 2009]. However, in the Jovian case, it is not obvious that the plasma cavities are the sources of the inertial effects [Mottez et al, 2010] and it is possible that they result from wave filamentation at the border of the Io plasma torus .…”
Section: Influence Of the Ion To Electron Mass Ratiomentioning
confidence: 99%
“…Recent works have been specifically devoted to non-MHD effects [Tsiklauri et al, 2005;McClements and Fletcher, 2009;Bian and Kontar, 2011]. There are also observational evidences that Alfvén waves can accelerate electrons in the vicinity of Io and Jupiter [Hess et al, 2007] sometimes combined with other acceleration structures [Hess et al, 2009]. However, in the Jovian case, it is not obvious that the plasma cavities are the sources of the inertial effects [Mottez et al, 2010] and it is possible that they result from wave filamentation at the border of the Io plasma torus .…”
Section: Influence Of the Ion To Electron Mass Ratiomentioning
confidence: 99%
“…This perturbation propagates along the field lines as Alfvén waves [Neubauer, 1980;Goertz, 1983;Saur, 2004] from the satellite to the planet ionosphere, where it generates emissions spanning the spectrum from low-frequency radio to UVs [Bigg, 1964;Connerney et al, 1993;Clarke et al, 1996;Prangé et al, 1996;Clarke et al, 2002;Grodent et al, 2009;Wannawichian et al, 2010]. Alfvén waves accelerate electrons that excite the auroral emissions [Jones and Su, 2008;Swift, 2007;Hess et al, 2007Hess et al, , 2010. In the Io case, Hess et al [2010] showed that the turbulent filamentation of the Alfvén wave close to the satellite, seen by Chust et al [2005], is necessary to explain the observed power of the emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale Alfvén waves are trapped in the wings, which cause particle acceleration (Su et al 2003;Ergun et al 2006) and decametric radiation (Hess et al 2007(Hess et al , 2008(Hess et al , 2009). In the highly relativistic pulsar wind, the acceleration and emission process may be quite different from those arising in the vicinity of Jupiter, but the current A125, page 3 of 8 A&A 555, A125 (2013) neutron star I A certainly constitutes an important source of free energy for radio emissions.…”
Section: Radio Emissionsmentioning
confidence: 99%